A robust numerical method for granular hydrodynamics in three dimensions - Shakeri, Ali; Schiochet Nasato, Daniel; Müller, Patric; Torres Menendez, Harol; Pöschel, Thorsten (Journal of Fluid Mechanics, 2021)
Granular systems are of a discrete nature. Nevertheless, it can be advantageous to describe their dynamics by means of continuum mechanical methods. The numerical solution of the corresponding hydrodynamic equations is, however, difficult. Therefore, previous numerical simulations are typically geared towards highly specific systems and frequently restricted to two dimensions or mild driving conditions. Here, we present the first robust general simulation scheme for granular hydrodynamics in three dimensions which is not bound to the above limitations. The performance of the simulation scheme is demonstrated by means of three applications which have been proven as notoriously difficult for numerical hydrodynamic description. Although, by construction, our numerical method covers grain-inertia flows, the presented examples demonstrate that it produces reliable results even in the jammed or high density limit.
CRIS-Team Scopus Importer:2021-05-14
Keywords: granular media

Automated Tomographic Assessment of Structural Defects of Freeze-Dried Pharmaceuticals - Müller, Patric; Sack, Achim; Dümler, Jens; Heckel, Michael; Wenzel, Tim; Siegert, Teresa; Schuldt-Lieb, Sonja; Gieseler, Henning; Pöschel, Thorsten (Aaps Pharmscitech, 2024)
The topology and surface characteristics of lyophilisates significantly impact the stability and reconstitutability of freeze-dried pharmaceuticals. Consequently, visual quality control of the product is imperative. However, this procedure is not only time-consuming and labor-intensive but also expensive and prone to errors. In this paper, we present an approach for fully automated, non-destructive inspection of freeze-dried pharmaceuticals, leveraging robotics, computed tomography, and machine learning.
CRIS-Team Scopus Importer:2024-07-05
Keywords: freeze-drying; lyopohilisate; non-destructive inspection; X-ray tomography

Circular ratchets as transducers of vertical vibrations into rotations - Heckel, Michael; Müller, Patric; Pöschel, Thorsten; Gallas, Jason (Physical Review E, 2012)
Granular ratchets are well-known devices that when driven vertically produce a counterintuitive horizontal transport of particles. Here we report the experimental observation of a complementary effect: the striking ability of circular ratchets to convert their vertical vibration into their own rotation. The average revolution speed shows a maximum value for an optimal tooth height. With no special effort the rotation speed could be maintained steady during several hours. Unexpected random arrests and reversals of the velocity were also observed abundantly. © 2012 American Physical Society.

Collective granular dynamics in a shaken container at low gravity conditions - Kollmer, Jonathan; Sack, Achim; Heckel, Michael; Zimber, Fabian; Müller, Patric; Bannerman, Marcus; Pöschel, Thorsten (7th International Conference on Micromechanics of Granular Media: Powders and Grains 2013, 2013)
We investigate the collective dissipative behavior of a model granular material (steel beads) when subjected to vibration. To this end, we study the attenuation of the amplitude of an oscillating leaf spring whose free end carries a rectangular box partly filled with granulate. To eliminate the perturbing influence of gravity, the experiment was performed under conditions of microgravity during parabolic flights. Different regimes of excitation could be distinguished, namely, a gas-like state of disordered particle motion and a state where the particles slosh back and forth between the container walls in a collective way, referred to as collect-and-collide regime. For the latter regime, we provide an expression for the container size leading to maximal dissipation of energy, that also marks the transition to the gas like regime. Also for systems driven at fixed amplitude and frequency, we find both the gas regime and the collect-and-collide regime resulting in similar dissipative behavior as in the case of the attenuating vibration. © 2013 AIP Publishing LL
Keywords: damping; Granular material

Collision of viscoelastic spheres: Compact expressions for the coefficient of normal restitution - Müller, Patric; Pöschel, Thorsten (Physical Review E, 2011)
The coefficient of restitution of colliding viscoelastic spheres is known analytically as a complete series expansion in terms of the impact velocity where all (infinitely many) coefficients are known. While being analytically exact, this result is not suitable for applications in efficient event-driven molecular dynamics (eMD) or direct simulation Monte Carlo (DSMC) methods. Based on the analytic result, here we derive expressions for the coefficient of restitution that allow for application in efficient eMD and DSMC simulations of granular systems. © 2011 American Physical Society.

Complex velocity dependence of the coefficient of restitution of a bouncing ball - Müller, Patric; Heckel, Michael; Sack, Achim; Pöschel, Thorsten (Physical Review Letters, 2013)
We investigate the coefficient of normal restitution as a function of the impact velocity, ε(v), for inelastic spheres. We observe oscillating behavior of ε(v) which is superimposed to the known decay of the coefficient of restitution as a function of impact velocity. This remarkable effect was so far unnoticed because under normal circumstances it is screened by statistical scatter. We detected its clear signature by recording large amounts of data using an automated experiment. The new effect may be understood as an interplay between translational and vibrational degrees of freedom of the colliders. Both characteristics of the oscillation, the wavelength and the amplitude, agree quantitatively with a theoretical description of the experiment. © 2013 American Physical Society.

Contact of granular particles and the simulation of rapid flows using event-driven molecular dynamics - Pöschel, Thorsten; Brilliantov, Nikolai; Formella, Arno; Heckel, Michael; Kruelle, Christof; Müller, Patric; Salueña, Clara; Schwager, Thomas (European Journal of Environmental and Civil Engineering, 2008)
We discuss several models for granular particles commonly used in Molecular Dynamics simulations of granular materials, including spheres with linear dashpot force, viscoelastic spheres and adhesive viscoelastic spheres. Starting from the vectorial interaction forces we derive the coefficients of normal and tangential restitution as functions of the vectorial impact velocity and of the material constants. We review the methods of measurements of the coefficients of restitution and characterize the coefficient of normal restitution as a fluctuating quantity. Moreover, the scaling behavior and the influence of different force laws on the dynamical system behavior are discussed. The powerful method of event-driven Molecular Dynamics is described and the algorithmic simulation technique is explained in detail. Finally we discuss the limitations of event-driven MD.

Coupled Simulation of Deformable Bodies and ISPH Fluids for Secondary Bone Healing - Aburumman, Nadine; Müller, Patric; Nair, Prapanch; Pöschel, Thorsten (Eurographics technical report series, 2017)
We propose a new scheme for the two-way coupling of incompressible fluids and deformable bodies, where we focus on a medical application; in particular, secondary bone healing. Our method allows for accurate simulation and visualisation of the secondary bone healing process, which is used to optimise clinical treatment of bone fractures. In our simulation, the soft tissues are simulated as elastic materials using Strain Based Dynamics (SBD), and fluid is simulated using Incompressible Smoothed Particle Hydrodynamics (ISPH). The interaction model we propose works with any type of deformation technique as long as the object surface is represented by a polygonal mesh and the fluid by Lagrangian particles.

DEM9 Book of Abstracts - Angelidakis, Vasileios; D'Angelo, Olfa; Müller, Patric; Pöschel, Thorsten; Roy, Sudeshna; Xiao, Hongyi (2023)
DEM9 addressed the latest advancements in the simulation of particulate systems using discrete element methods, including coupled simulations, particle fragmentation, non-spherical particles, multiscale and multiphase systems.<br

"Do touch!" - 3D Scanning and Printing Technologies for the Haptic Representation of Cultural Assets: A Study with Blind Target Users - Bruns, Arne; Spiesberger, Anika A.; Triantafyllopoulos, Andreas; Müller, Patric; Schuller, Björn W. (SUMAC 2023 - Proceedings of the 5th Workshop on the analySis, Understanding and proMotion of heritAge Contents, 2023)
Visiting museums can be challenging for visually impaired people, as many objects are hidden behind glass walls and information is limited to descriptions. One of the best ways to increase accessibility and inclusion in museums and other cultural heritage institutions is through the use of 3D-printed replicas. However, there are several different scanning and printing processes that not only differ in terms of effort and cost but can also produce very different results. This paper evaluates two different scanning techniques and four different printing processes in terms of these aspects and includes feedback from a group of blind and partially sighted users on the aesthetic quality and fidelity of the printed objects. We found differences between the scanning methods mainly regarding their ease of use. Of the printing methods tested, stereolithography was preferred by the majority of participants for use in the museum. Additionally, we include user comments which touch on the general aspects of presenting museum artefacts using haptic devices. Our study thus provides valuable insights into the preferences of the target users, which can be used to inform decisions about more inclusive museum experiences.
CRIS-Team Scopus Importer:2023-12-15
Keywords: 3d printing processes; 3d scanning methods; blind and partially sighted; cultural heritage

Dynamical regimes and stability of circular granular ratchets - Müller, Patric; Gallas, Jason; Pöschel, Thorsten (Scientific Reports, 2017)
Ratchets are simple mechanical devices which combine spatial asymmetry and nonequilibrium to produce counterintuitive transport of particles. The operation and properties of linear ratchets have already been extensively explored. However, very little is known about circular granular ratchets, startling devices able to convert vertical vibrations into rotations of the device. Here, we report results of systematic numerical investigations of the operational characteristics of circular granular ratchets. Several distinct behaviors are identified and explained in terms of the inner flow fields of the ratchet. All dynamical regimes found are robust and should not be difficult to observe in laboratory experiments.

Erratum to: Stability of freeze-dried products subjected to microcomputed tomography radiation doses - Wenzel, Tim; Sack, Achim; Müller, Patric; Pöschel, Thorsten; Schuldt-Lieb, Sonja; Gieseler, Henning (Journal of Pharmacy and Pharmacology, 2022)
CRIS-Team Scopus Importer:2022-03-11

Event-driven DEM of soft spheres - Pöschel, Thorsten; Müller, Patric (7th International Conference on Micromechanics of Granular Media: Powders and Grains 2013, 2013)
In this paper an algorithm is described which combines the efficiency of event-driven Molecular-Dynamics (eMD) and the physical correctness of force-based Molecular-Dynamics (MD) for dilute granular systems of frictionless spheres. © 2013 AIP Publishing LL
Keywords: event-driven Molecular-Dynamics; granular Gases; hard-sphere model; Molecular-Dynamics

Event-driven molecular dynamics of soft particles - Müller, Patric; Pöschel, Thorsten (Physical Review E, 2013)
The dynamics of dissipative soft-sphere gases obeys Newton's equations of motion, which are commonly solved numerically by (force-based) Molecular Dynamics (MD) schemes. With the assumption of instantaneous, pairwise collisions, the simulation can be accelerated considerably using event-driven MD, where the coefficient of restitution is derived from the interaction force between particles. Recently it was shown, however, that this approach may fail dramatically, that is, the obtained trajectories deviate significantly from the ones predicted by Newton's equations. In this paper, we generalize the concept of the coefficient of restitution and derive a numerical scheme which, in the case of dilute systems and frictionless interaction, allows us to perform highly efficient event-driven MD simulations even for noninstantaneous collisions. We show that the particle trajectories predicted by our scheme agree perfectly with the corresponding (force-based) MD, except for a short transient period whose duration corresponds to the duration of the contact. Thus, the new algorithm solves Newton's equations of motion like force-based MD while preserving the advantages of event-driven simulations. © 2013 American Physical Society.

Granular jet impact: Probing the ideal fluid description - Müller, Patric; Formella, Arno; Pöschel, Thorsten (Journal of Fluid Mechanics, 2014)
We investigate the impact of a granular jet on a finite target by means of particle simulations. The resulting hydrodynamic fields are compared with theoretical predictions for the corresponding flow of an incompressible and rotation-free fluid. The degree of coincidence between the field obtained from the discrete granular system and the idealized continuous fluid flow depends on the characteristics of the granular system, such as granularity, packing fraction, inelasticity of collisions, friction and target size. In certain limits we observe a granular-continuum transition under which the geometric and dynamic properties of the particle jet and the fluid jet become almost identical. © 2014 Cambridge University Press.
Keywords: complex fluids; granular media; jets

ISPH–PBD: coupled simulation of incompressible fluids and deformable bodies - Abu Rumman, Nadine; Nair, Prapanch; Müller, Patric; Barthe, Loïc; Vanderhaeghe, David (Visual Computer, 2020)
We present an efficient and stable method for simulating the two-way coupling of incompressible fluids and deformable bodies. In our method, the fluid is represented by particles, and simulated using divergence-free incompressible smoothed-particle hydrodynamics (ISPH). The deformable bodies are represented by polygonal meshes, where the elastic deformations are simulated using a position-based dynamics scheme. Our technique enforces incompressibility on the fluid using divergence-free constraints on the velocity field, while it effectively simulates the physical features of deformable bodies. Most current ISPH methods are struggling with the issue of free-surface boundary conditions. We handle this problem by introducing a novel free-surface formulation, where our free-surface model obviates the need to identify the surface particles. For the interaction between the fluid and the deformable solids, we model the forces that both phases, fluid and solid, exert upon each other. We demonstrate that our approach effectively handles complex coupling scenarios between fluids and thin deformable shells or highly deformable solids, and produces plausible results.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Deformable bodies; Fluids; ISPH; PBD; Thin shells

Misconceptions about gyroscopic stabilization - Müller, Patric; Sack, Achim; Pöschel, Thorsten (American Journal of Physics, 2020)
A spinning gyroscope resists small torques in directions perpendicular to its axis, that is, the angular orientation of a body rigidly attached to a gyroscope is stable against rotation around certain axes. Since the angular orientation of a body is described by three angles (e.g., Euler angles), one might conclude that it is possible to stabilize the orientation of an object against rotation using a combination of three gyroscopes spinning around non-collinear axes. We perform experiments under conditions of weightlessness to demonstrate that systems of coupled gyroscopes cannot arrest the angular orientation of free-floating objects, in contradiction to a widespread myth about gyroscopic stabilization, based on the above arguments. (C) 2020 American Association of Physics Teachers.
CRIS-Team WoS Importer:2020-06-26

Mixing of rarefied gases in T-shape micromixers - Hussain, Mubashir; Pöschel, Thorsten; Müller, Patric (Applied Thermal Engineering, 2019)
We study the mixing of rarefied gases in a T-shape micromixer by means of fully three-dimensional Monte-Carlo direct simulations. In contrast to previous 2D-results, the characteristics of the channel walls (thermal or specular) have significant effect on the mixing efficiency. For the 3D case, we characterize the mixing efficiency in dependence on temperature and mass density of the gases. Based on kinetic theory arguments, we develop a theoretical model in good agreement with the simulation results. In particular, the theoretical prediction of system size scaling agrees well with the simulation.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Discrete simulation Monte-Carlo; Mixing; Rarefied flows; Simulation; T-shape

Model geometries of random porous materials - Buchele, Felix; Blank, Michael; Pöschel, Thorsten; Müller, Patric (International Journal of Heat and Mass Transfer, 2024)
We describe a method for modeling the geometry of random porous materials. The approach enables the independent selection of crucial parameters, including porosity, pore size distribution, pore shape, and connectivity. Consequently, it can effectively model a wide range of porous systems. Due to the diverse and systematic variation possibilities, the method is suitable for developing and optimizing porous structures. The geometries can be exported as triangular meshes, facilitating their immediate use in numerical simulation and further digital processing. We showcase the method's capabilities by minimizing the foam structure's thermal conductivity through geometry optimization.
CRIS-Team Scopus Importer:2024-08-30
Keywords: Numerical modeling; Numerical simulation; Porous geometry; Porous systems; Topology optimization

Movers and shakers: Granular damping in microgravity - Bannerman, Marcus; Kollmer, Jonathan; Sack, Achim; Heckel, Michael; Müller, Patric; Pöschel, Thorsten (Physical Review E, 2011)
The response of an oscillating granular damper to an initial perturbation is studied using experiments performed in microgravity and granular dynamics simulations. High-speed video and image processing techniques are used to extract experimental data. An inelastic hard sphere model is developed to perform simulations and the results are in excellent agreement with the experiments. In line with previous work, a linear decay of the amplitude is observed. Although this behavior is typical for a friction-damped oscillator, through simulation it is shown that this effect is still present even when friction forces are absent. A simple expression is developed which predicts the optimal damping conditions for a given amplitude and is independent of the oscillation frequency and particle inelasticities. © 2011 American Physical Society.

Negative coefficient of normal restitution - Müller, Patric; Krengel, Dominik; Pöschel, Thorsten (Physical Review E, 2012)
This paper shows that negative coefficients of normal restitution occur inevitably when the interaction force between colliding particles is finite. We derive an explicit criterion showing that for any set of material properties there is always a collision geometry leading to negative restitution coefficients. While from a phenomenological point of view, negative coefficients of normal restitution appear rather artificial, this phenomenon is generic and implies an important overlooked limitation of the widely used hard sphere model. The criterion is explicitly applied to two paradigmatic situations: for the linear dashpot model and for viscoelastic particles. In addition, we show that for frictional particles the phenomenon is less pronounced than for smooth spheres. © 2012 American Physical Society.

Oblique impact of frictionless spheres: On the limitations of hard sphere models for granular dynamics - Müller, Patric; Pöschel, Thorsten (Granular Matter, 2012)
When granular systems are modeled by hard spheres, particle-particle collisions are considered as instantaneous events. This implies that while the velocities change according to the collision rule, the positions of the particles are the same before and after such an event. We show that depending on the material and system parameters, this assumption may fail. For the case of viscoelastic particles we present a universal condition which allows to assess whether hard-spheremodeling and, thus, event-driven Molecular Dynamics simulations are justified. © Springer-Verlag 2012.
Keywords: Coefficient of normal restitution; Event-driven molecular dynamics; Granular gases; Hard sphere model; Viscoelastic spheres

Particle size segregation in granular pipe flow - Müller, Patric; Panchenko, Artem; Ku, Wing To; Pöschel, Thorsten (Chaos, 2025)
The flow of granular material through pipes is characterized by significant variations in solid fraction (density waves) along the pipe. Previously, it has been shown that this intermittent flow behavior can be mitigated by adding a texture to the pipe’s inner wall. This work shows that adding surface roughness can lead to particle size segregation as a side effect in bidisperse systems. Using particle simulations, we characterize the parameter ranges in which segregation occurs.
CRIS-Team Scopus Importer:2025-05-02

Ping-pong ball cannon: Why do barrel and balls fly in the same direction? - Pöschel, Thorsten; Nasato, Daniel S.; Parteli, Eric J. R.; Gallas, Jason; Müller, Patric (American Journal of Physics, 2019)
An impressive ping-pong ball cannon can be made by placing a bottle of liquid nitrogen at the bottom of a container and quickly covering it with, say, 1500 ping-pong balls. The liquid turns rapidly into a gas whose mounting pressure explodes the bottle, sending a swarm of balls upward out of the container. Surprisingly, the container also moves upward. This is a counterintuitive effect because the balance of forces, that is, Newton's third law does not seem to allow the container to move upwards. We explain the effect as a consequence of granular jamming in combination with Coulomb's friction law. (C) 2019 American Association of Physics Teachers.
CRIS-Team WoS Importer:2019-04-04

Rarefied reactive gas flow in T-shape microreactors - Hussain, Mubashir; Müller, Patric (Applied Thermal Engineering, 2020)
The present study investigates the reactive gas flows in T-shape microreactors by means of a 3D direct simulation Monte-Carlo method (DSMC). The reactive process is modeled by incorporating a single step irreversible exothermic reaction of gas species A and B. The energy released in each reaction is added to the system by increasing the kinetic energy of the product gas specie C. The reactive collisions are modeled by means of a momentum preserving hard sphere collision model in 3D DSMC. We analyzed several process and gas parameters to observe their extent of influence on the characteristics of the reactive flow. The T-microreactor with thermal walls showed much higher mass carrying capacity as compared to the specular walls. The reaction front, which initially for maximum reaction rate was close to the inlet of gas specie of higher mass density, moved towards the center of the inlet part of the T-channel and eventually dissolved with decreasing reaction rates. This transition was smooth in the T-channel with thermal walls, whereas, quite abrupt in case of specular walls. Moreover, in T-microreactors with thermal walls, the amount of A and B converted to C follows an exponential decrease especially in moderate to low reaction rates. Further, with a clear separation between high and low reactive regimes, a piece-wise exponential decay in concentration of C with respect to decreasing reaction rates was also observed in the T-channel with specular walls.
CRIS-Team Scopus Importer:2020-12-11
Keywords: DSMC; Gas flow; Microreactor; Reactive flow; T-shape

Soft particles reinforce robotic grippers: robotic grippers based on granular jamming of soft particles - Götz, Holger; Santarossa, Angel; Sack, Achim; Pöschel, Thorsten; Müller, Patric (Granular Matter, 2022)
Granular jamming has been identified as a fundamental mechanism for the operation of robotic grippers. In this work, we show, that soft particles like expanded polystyrene beads lead to significantly larger gripping forces in comparison to rigid particles. In contradiction to naive expectation, the combination of jamming and elasticity gives rise to very different properties of the jammed phase, compared to hard-particle systems. This may be of interest also beyond the application in robotic grippers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Granular gripper; Granular jamming; Soft robotics

Two-ball problem revisited: Limitations of event-driven modeling - Müller, Patric; Pöschel, Thorsten (Physical Review E, 2011)
The main precondition of simulating systems of hard particles by means of event-driven modeling is the assumption of instantaneous collisions. The aim of this paper is to quantify the deviation of event-driven modeling from the solution of Newton's equation of motion using a paradigmatic example: If a tennis ball is held above a basketball with their centers vertically aligned, and the balls are released to collide with the floor, the tennis ball may rebound at a surprisingly high speed. We show in this article that the simple textbook explanation of this effect is an oversimplification, even for the limit of perfectly elastic particles. Instead, there may occur a rather complex scenario including multiple collisions which may lead to a very different final velocity as compared with the velocity resulting from the oversimplified model. © 2011 American Physical Society.

VERFAHREN SOWIE EIN GRAPHEN-GENERATOR ZUM ERZEUGEN EINES GRAPHEN DER BEZIEHUNGEN ZWISCHEN OBJEKTEN IN NETZWERKEN BESCHREIBT - Pöschel, Thorsten; Lehmann, Heiko; Mühlbauer, Sebastian; Müller, Patric; Blank, Michael; Schmiedeberg, Michael (2021)
Die Erfindung betrifft ein Verfahren, einen Graphen-Generator zum Erzeugen eines Graphen sowie ein Computersystem auf welchem der erzeugte Graph simuliert werden kann.
Keywords: Netzwerk; Graph; Epidemie; Computervirus; statistisches Verfahren